Quantificação e avaliação dos resultados de exames papanicolau não buscados nas Unidades de Saúde da Família em Altamira-Pará - SALES, Hemily da Silva (2024)
The objective of this research is to present data related to the effectiveness of cervical cancer screening in the municipality of Altamira, located in the interior of the state of Pará, through the quantification and evaluation of the results of preventive exams for cervical cancer that were not sought between the years 2018 and 2021. This is a retrospective descriptive study with a quantitative approach, carried out in the Family Health Units in the urban area of Altamira. The target population consisted of women who underwent the Papanicolaou test and who did not return to receive the result of their analysis. Data were obtained from the Cancer Information System (SISCAN) and also from results filed at health services. The following variables were analyzed: number of exams performed, number of exams not delivered, women's age group and the result of the cervical cancer preventive exam, with regard to cytological characteristics and microbiology. In the period from 2018 to 2021, there were 26,267 exams performed and 2,658 exams not sought. The average non-return rate was 10.63%. According to data from the Ministry of Health, 30.81% of women are outside the age range indicated for screening for this cancer. In addition, 31.3% of the patients whose microbiology was investigated had pathogenic microorganisms associated with the progression of HPV infection, with emphasis on Gardnerella vaginalis, and 78.57% of the exams with precursor alterations of cervical cancer showed the same microbiology profile. There is no control over the age range of women who undergo the Papanicolaou test, the frequency with which they are screened for this neoplasm and the guarantee of their return to evaluate the result. The correct investigation of women within the target group with adequate follow-up of the identified lesions or precursor alterations has a greater impact on mortality rates than coverage rates.